The laboratory of European integration: The Benelux Union: history, institutions, goals - Kőváriné Ignáth, Éva (POLARITIES, 2026)
2025 witnessed the 15th anniversary of the cooperation of Belgium, the Netherlands, and Luxembourg within the Benelux Union. The history of cooperation between the three countries dates back even further, to their customs union agreement in 1944, which made them the first subregional cooperation in Europe. The formation of the Benelux Economic Union in 1958 indicated the strengthening of relations among the member states, and this cooperation is unique in the sence, that it is explicitly mentioned in the treaties of the European Union. The Benelux countries were at a crossroads at the beginning of the 21st century, facing taking a decision about the continuation of their cooperation. They ultimately opted to maintain it, and the three states signed the treaty establishing the Benelux Union. The goal of this study is to explore the history and evolution of cooperation between the three Benelux countries on the European continent, providing a comprehensive overview of the organisation and examining its current role and objectives.